Levels of Burnout and Its Determinant Factors Among Nurses in Private Hospitals of Addis Ababa, Ethiopia, Ethiopia, 2020. A Multi Central Institutional Based Cross Sectional Study - Feleke, Dejen Getaneh; Chanie, Ermiase Sisay; Hagos, Misganaw Girma; Derseh, Behailu Tariku; Tassew, Sheganew Fetene (Frontiers in Public Health, 2022)
Abstract Background: Burnout among nurses is a significant problem in healthcare establishments and has negative implications on clinical outcomes. International studies have shown the prevalence of burnout ranged from 10% to 70%. However, this is unknown among nurses in private hospitals in Addis Ababa. The study was intended to assess the levels of burnout and associated factors among nurses working in private hospitals, Addis Ababa, Ethiopia, 2020. Methods: Institution based cross-sectional study was used. A probability sampling specifically simple random sampling technique was employed to collect data and the Maslach burnout inventory human services survey (MBI-HSS) instrument was adapted to measure the levels of burnout. The data obtained was edited manually and entered into EPI- data version 4.6, then exported to SPSS version 25 for analysis. Logistic regression was used to identify association between dependent and independent variables and variables with p-value < 0.25 on bivariate analysis was taken into multivariate logistic regression then variables with P-value < 0.05 was considered as statistically significant. Result: A total of 385 questionnaires were distributed to participants, but 368 (96%) of them were collected and included in this study. The majority 56% and 69.8% of them were females and belonged to the age group of 20-29 years respectively. Two hundred seven (56.5%) of them reported suffering from a high level of burnout. In the multivariate logistic regression analysis, night duty shift [AOR=2.699; 95% CI: (1.043-6.987)], excessive workload [AOR=6.013; 95% CI: (3.016-11.989)], staff shortage [AOR=6.198; 95% CI: (3.162-12.147)], persistent interpersonal conflict [AOR=2.465; 95%CI: (1.225-4.961)] and nurses poor health status [AOR=3.4878; 95% CI: (1.815-8.282)] demonstrated a statistical significant association with the professional burnout. Conclusions and recommendations: Nurses’ burnout in private hospitals of Addis Ababa was highly prevalent. Therefore, ensure adequate staffing and minimize the work load of nurse’s professionals are mandatory to prevent it.